1996
DOI: 10.1520/jfs13932j
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Medical Examiner Cases in Which Methadone Was Detected, Harris County, Texas, 1987–1992

Abstract: In 1991, media reports of an increase in the number of deaths attributed to methadone toxicity in Harris County, Texas, raised public concern about the safety of methadone. This concern was heightened by publicity surrounding the closure of three Harris County methadone maintenance treatment programs due to their poor compliance with federal methadone regulations. In response to this concern, the Texas Department of Public Health requested that the Centers for Disease Control and Prevention (CDC) assist in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
8
29
0
4
Order By: Relevance
“…In retrospective evaluations of post mortem toxicological investigations over a fi ve-year period in France (Pirnay et al 2004) and 1 1-year period in Germany (Grab et al 2003) a large proportion of methadone deaths were found to occur in combination with opioids, benzodiazepines or alcohol. Similar results have also been reported from the US (Barrett et al 1996), Australia (Capel hom & Drummer 2002), Switzerland (Parret et al 2000), and England, Wales and Scotland (Ghodse et al 2003;Griffith 2004;Seymour et al . 2003)…”
Section: Methadone Deat Hssupporting
confidence: 77%
“…In retrospective evaluations of post mortem toxicological investigations over a fi ve-year period in France (Pirnay et al 2004) and 1 1-year period in Germany (Grab et al 2003) a large proportion of methadone deaths were found to occur in combination with opioids, benzodiazepines or alcohol. Similar results have also been reported from the US (Barrett et al 1996), Australia (Capel hom & Drummer 2002), Switzerland (Parret et al 2000), and England, Wales and Scotland (Ghodse et al 2003;Griffith 2004;Seymour et al . 2003)…”
Section: Methadone Deat Hssupporting
confidence: 77%
“…Este sector de población tiende a consumir todo tipo de drogas psicoactivas, con el consecuente riesgo de sobredosis por potenciación de sus efectos y/o aumento de sus niveles. Precisamente es el alcohol junto a las benzodiacepinas, una de las combinaciones encontradas con mayor frecuencia en las muertes relacionadas con la metadona (25,26). La trascendencia de esta combinación queda subrayada por el hallazgo de menores concentraciones plasmáticas de metadona con defunciones relacionadas con alcohol que en aquellas en que éste no estuvo presente, a pesar de que las primeras sólo constituyeron un 30% de los casos en este estudio (27).…”
Section: Alcoholunclassified
“…Methadone toxicity ranks high among the list of problems cited by opponents of methadone treatment (e.g., Marks, 1994;Newcombe, 1996), and periodic outbreaks of methadone-related deaths (Barrett et al, 1996;Drummer et al, 1992;Zimney & Luke, 1981) appear to lend credence to these critics. In contrast, standard substance abuse textbooks (Senay, 1994;Lowinson et al, 1992) often emphasize the safety of methadone in the treatment of opioid dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Death directly attributable to methadone toxicity is, in fact, rare among patients on maintenance (Baden, 1970;Barrett et al, 1996;Chappel, Mays & Senay, 1973;Concool, Smith, & Stimmel, 1979;Des Jarlais, 1984;Greene, Luke & DuPont, 1974;Kreek, 1973;Manning et al, 1976;Texas Department of Health, unpublished). When such deaths do occur, they tend to happen during induction to maintenance, when assessment of patients' tolerance to opioids and concurrent use of other substances is especially problematic (Drummer et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation